Mapping Of Strategies And Methods For Learning Arabic Speaking Skills - Roziqi, Muhammad Ainur; Murdiono, Murdiono; Rahman, Nur Fuadi; Arif, Muhammad (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to map and identify research developments on strategies and methods of learning Arabic speaking skills in Indonesia. This qualitative literature review approach study analyzed data sources through journal articles on Arabic studies from 2019-2023. The results show that the amount of research from 2019-2023 has fluctuated in the number of articles published. During this time, qualitative methods were used most in the study. The most discussed topics are learning, improving strategies, and using direct methods of speaking most discussed. The variety of research objects shows that junior high school students are the most dominant research objects. In addition, in terms of the most common problems, namely the low ability of students to speak Arabic and students' difficulty in speaking Arabic, the main factor that makes learning speaking skills less effective is the application of inappropriate learning methods, such as the al-Qawaid wa al-Tarjamah method, the lecture and reading method, and the application of monotonous and less varied strategies and methods. Likewise, teachers' lack of competence in applying various fun methods results in teachers being more active than students.